PROFITABILITY, LEVERAGE RATIO, AND LIQUIDITY TO FIRM VALUE WITH GENDER DIVERSITY AS A MODERATING VARIABLE - Dwi Aprillia Rahmawati; Sarwenda Biduri; Imelda Dian Rahmawati (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine whether gender diversity moderates the effects of profitability, leverage ratio, and liquidity on firm value in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the 2017–2023 period. Methods: Using a quantitative approach, secondary data from annual financial reports were analyzed. A purposive sampling technique yielded 180 companies as the sample. The data were processed using SmartPLS version 3.0, which includes outer model testing for validity and reliability and inner model testing for hypothesis validation. Results: The findings reveal that profitability and leverage ratio significantly affect firm value, while liquidity does not. Gender diversity strengthens the relationship between profitability and firm value but does not moderate the effects of leverage ratio and liquidity on firm value. This indicates that gender diversity enhances managerial decision-making through women's detailed analysis and risk assessment skills. Novelty: This research highlights the moderating role of gender diversity in the relationship between profitability and firm value, underscoring the strategic importance of diverse corporate governance. These findings provide practical insights for companies aiming to improve their value by integrating profitability-focused strategies and fostering gender diversity on boards.